Impact of COVID-19 Pandemic on Undergraduate Psychiatry Teaching, Educational Environment, and Learning Processes - Chew QH (Dove Medical Press, 2021)
Qian Hui Chew,1 Kang Sim2 1Research Division, Institute of Mental Health, Singapore; 2West Region and Education Office, Institute of Mental Health, SingaporeCorrespondence: Kang SimInstitute of Mental Health, 10 Buangkok View, 539747, SingaporeTel +65 6389 2000Email kang_sim@imh.com.sgPurpose: The COVID-19 pandemic has brought about significant changes in the way undergraduate medical education is conducted including psychiatry teaching. In view of sparse data on how the perception of the undergraduate educational environment (EE) is affected by the pandemic, we sought to compare the ratings of EE and learning processes (motivation, engagement, equipping, appreciation of psychiatry) between the 2020 (during pandemic) and 2019 (before pandemic) cohorts of students, and examined how the perception of the EE would influence overall experience within the psychiatry rotation.Patients and Methods: The DREEM (Dundee Ready Education Environment Measure) was administered to fourth-year medical undergraduate students undergoing a psychiatry rotation in 2020 during the pandemic and these ratings were compared with those of the preceding cohort in 2019. Students also completed five additional items evaluating various learning processes and overall rating of the posting. Relationships between the DREEM scores, learning processes, and overall effectiveness of rotation were assessed using correlation and mediational analyses.Results: Altogether, 84 (response rate 93.3%) and 269 (response rate 89.7%) medical undergraduates participated in the study from 2020 and 2019 cohorts, respectively. The 2020 cohort had higher scores on the total DREEM (p = 0.032), academic self-perception DREEM subscale (p = 0.002), felt more engaged (p = 0.043) and better equipped (p = 0.003) compared with the 2019 cohort. Overall, DREEM and subdomain scores correlated significantly with specific learning processes. The direct effect of total DREEM and overall rating of psychiatry posting was significant in mediational analyses.Conclusion: Our results highlighted that students’ perception of the EE remained positive during the pandemic and impacts overall experience of the psychiatry posting. Undergraduate psychiatry training should continually seek to enhance the EE so as to optimize learning through better engagement and equipping of the learners even during the pandemic.Keywords: adult learning, medical education, undergraduate, situated learning